Sirtuin 2 aggravates postischemic liver injury by deacetylating mitogen‐activated protein kinase phosphatase‐1 - Wang, Jie (Hepatology, 2016)
Sirtuin 2 (Sirt2) is known to negatively regulate anoxia‐reoxygenation injury in myoblasts. Because protein levels of Sirt2 are increased in ischemia‐reperfusion (I/R)‐injured liver tissues, we examined whether Sirt2 is protective or detrimental against hepatic I/R injury. We overexpressed Sirt2 in the liver of C57BL/6 mice using a Sirt2 adenovirus. Wild‐type and Sirt2 knockout mice were subjected to a partial (70%) hepatic ischemia for 45 minutes, followed by various periods of reperfusion. In another set of experiments, wild‐type mice were pretreated intraperitoneally with AGK2, a Sirt2 inhibitor. Isolated hepatocytes and Kupffer cells from wild‐type and Sirt2 knockout mice were subjected to hypoxia‐reoxygenation injury to determine the in vitro effects of Sirt2. Mice subjected to I/R injury showed typical patterns of hepatocellular damage. Prior injection with Sirt2 adenovirus aggravated liver injury, as demonstrated by increases in serum aminotransferases, prothrombin time, proinflammatory cytokines, hepatocellular necrosis and apoptosis, and neutrophil infiltration relative to control virus‐injected mice. Pretreatment with AGK2 resulted in significant improvements in serum aminotransferase levels and histopathologic findings. Similarly, experiments with Sirt2 knockout mice also revealed reduced hepatocellular injury. The molecular mechanism of Sirt2's involvement in this aggravation of hepatic I/R injury includes the deacetylation and inhibition of mitogen‐activated protein kinase phosphatase‐1 and consequent activation of mitogen‐activated protein kinases. Conclusion: Sirt2 is an aggravating factor during hepatic I/R injury. (Hepatology 2017;65:225‐236).